Pit wall optimisation and effective wall management strategies at Invincible Open Pit, St Ives Gold Mines - Abdulai, M; Andrews, PG; McMahon, D; Bona, E; Walker, J (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The requirements for open pit wall optimisation are often reliant on the drive for maximum ore extraction while maintaining the stability of the individual benches and overall slopes. In a very basic sense, slope optimisation can mean increasing the slope angles and/or bench heights and deepening of the pit against the original design with an objective to integrate the allowable factor of safety into the mine planning. This exercise comes along with the implementation of effective wall management practices such as attaining operable berm catch capacity, drill and blast design practices and procedures that address poor batter condition. The optimisation of pit slopes to achieve a steep deep pit and still maintain slope stability is often seen as challenging without the integration of batter steepening trials within selected geotechnical domains to understand if the rock mass can support the steep slope strategies. The Invincible Open Pit is known for fair to good quality rocks and high porewater pressures. It was decided to change the slope configuration by adopting 20 m batters instead of 15 m, and to deepen the pit according to the experience gained with the slope from interim ‘staged’ pit walls. However, conducting drilling and blasting and wall excavation without having negative impact on the pit walls is a major geotechnical challenge. The paper will detail how the geotechnical team addressed this challenge and will demonstrate the improvement in the drilling, blasting and excavation of the walls leading to improved results in terms of safety and design reliability.
Keywords: pit slope optimisation